Cherokee Sister : The Collected Writings of Catharine Brown, 1818-1823 - Brown, Catharine, 1800?-1823 (Book collections on Project MUSE., 2014)
"A collection of writings by and about Catharine Brown, the first Cherokee to convert to Christianity who wrote extensively about her conversion and faith"--